A recognition of exosomes as regulators of epigenetic mechanisms in central nervous system diseases - Hu, Shunxin; Feng, Lei; Yang, Zhonghong; Fan, Xuechen; Gao, Haozheng; Yang, Tiancai (Frontiers in Molecular Neuroscience, 2024)
Exosomes, vesicular structures originating from cells, participate in the conveyance of proteins and nucleic acids. Presently, the centrality of epigenetic modifications in neurological disorders is widely acknowledged. Exosomes exert influence over various epigenetic phenomena, thereby modulating post-transcriptional regulatory processes contingent upon their constituent makeup. Consequently, the heightened attention directed toward exosomes as instigators of epigenetic alterations has burgeoned in recent years. Notably, exosomes serve as vehicles for delivering methyltransferases to recipient cells. More significantly, non-coding RNAs, particularly microRNAs (miRNAs), represent pivotal contents within exosomes, wielding the capacity to influence the expression of diverse factors within the cerebral milieu. The transfer of these exosomal contents amidst brain cells, encompassing neuronal cells and microglia, assumes a critical role in the genesis and progression of neurological disorders, also, this role is not limited to neurological disorders, it may deal with any human disease, such as cancer, and cardiovascular diseases. This review will concentrate on elucidating the regulation of exosome-induced epigenetic events and its subsequent ramifications for neurological diseases. A more profound comprehension of the involvement of exosome-mediated epigenetic regulation in neurological disorders contributes to a heightened awareness of the etiology and advancement of cerebral afflictions.